Result that last.. Leadership for literacy - Dorn Linda, Soffos Carla (Ron Blome)
This tape ilustrates the seven festures of comprehensive literacy model for school change. One of the most importent features is a curriculum for literacy, which places a high priority on reading and writing and includes six essential elements of a balanced literacy program. Authentic examples from classrooms and team meetings ilustrate the comprehensive nature of the change process.
Area-Documental
Keywords: Genero-Guías educativas